Epidemiology and Management of Distal Radioulnar Injuries at Hadji Boejasin General Hospital, Pelaihari - Pratama, Yudha; Iqbal, Muhammad (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Distal radius fracture is one of the most common fractures, especially in the elderly. This fracture often followed by an ulna fracture, causing interference with the distal radioulnar joint (DRUJ). The aim of this study is to provide an overview of DRUJ trauma management along with its indications. This research is a retrospective descriptive study. Data collection was carried out from the medical record data of DRUJ trauma patients who were treated through the ED of H. Boejasin General Hospital. There were 19 samples that met the inclusion criteria, aged 18-60 years. A total of 7 patients (36.84%) underwent ORIF, 12 patients (63.16%) LAC (91.67%), and 1 patient underwent SAC (8.33%). Surgery is the main choice of treatment by orthopedic surgeons for DRUJ trauma patients due to high impact injuries, while conservative management is sufficient for low impact injuries.